Gestational diabetic transcriptomic profiling of microdissected human trophoblast - Bari, M; Ngo, S; Bastie, C; Sheppard, A; Vatish, M (BioScientifica, 2016)
Gestational diabetes mellitus (GDM), the most common metabolic complication of pregnancy, is influenced by the placenta, and its prevalence directly increases with obesity. Therefore, to define the aetiology of GDM requires that the confounding influence of obesity and the heterogeneous nature of the placenta impairing accurate quantitative studies be accounted for. Using laser capture microdissection (LCM), we optimized RNA extraction from human placental trophoblast, the metabolic cellular interface between mother and foetus. This allowed specific transcriptomic profiling of trophoblast isolated from GDM, and obese and normal human placentae. Genome-wide gene expression analysis was performed on the RNA extracted from the trophoblast of GDM and obese and normal placentae. Forty-five differentially expressed genes (DEGs) specifically discriminated GDM from matched obese subjects. Two genes previously linked with GDM, pregnancy specific beta-1 glycoprotein 6 (PSG6) and placental system A sodium-dependent transporter system (SLC38A1), were significantly increased in GDM. A number of these DEGs (8 ubiquitin-conjugating enzymes (UBE) splice variants (UBE2D3 variants 1, 3, 4, 5, 6, 7, and 9) and UBE2V1 variant 4)) were involved in RNA processing and splicing, and a significant number of the DEGs, including the UBE variants, were associated with increased maternal fasting plasma glucose.It is concluded that DEGs discriminating GDM from obese subjects were pinpointed. Our data indicate a biological link between genes involved in RNA processing and splicing, ubiquitination, and fasting plasma glucose in GDM taking into account obesity as the confounder.